2016
DOI: 10.2147/jmdh.s107796
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical domains framework to assess barriers to change for planning health care quality interventions: a systematic literature review

Abstract: BackgroundTheoretical domains framework (TDF) provides an integrative model for assessing barriers to behavioral changes in order to suggest interventions for improvement in behavior and ultimately outcomes. However, there are other tools that are used to assess barriers.ObjectiveThe objective of this study is to determine the degree of concordance between domains and constructs identified in two versions of the TDF including original (2005) and refined version (2012) and independent studies of other tools.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 55 publications
0
26
1
Order By: Relevance
“…As reviews by Lau et al [ 7 , 8 ] have shown, changes in policy direction, organisational turbulence and the exigencies of everyday work in complex healthcare settings, all affect implementation processes. Such problems are also consistently shown to be centrally important in studies informed by psychological theories [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As reviews by Lau et al [ 7 , 8 ] have shown, changes in policy direction, organisational turbulence and the exigencies of everyday work in complex healthcare settings, all affect implementation processes. Such problems are also consistently shown to be centrally important in studies informed by psychological theories [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most findings of influences on evidence use surfaced by the TDF agree with ones mentioned in the literature, whilst a few disagreed. The high relevance of Belief About Consequences coincides with findings showing that healthcare professionals tend to act on knowledge if they believe it will have positive consequences for the care of patients (or not act upon it in the case of anticipated negative outcomes) [11, 3840]. The strong influence on KBs of the anticipated health outcomes resulting from evidence use may link to the fact that many KBs in the study had hybrid professional roles, including responsibility for applying knowledge (such as through healthcare service delivery) as well as knowledge brokering.…”
Section: Discussionmentioning
confidence: 54%
“…The Theoretical Domains Framework has proven to be a useful tool for a systematic approach to identify barriers in work processes, contributing to the planning of more effective interventions by recognizing that barriers have different natures and therefore require different interventions. In this research, the model was used to identify which barriers impact the possibility of performing comprehensive care for overweight individuals in primary care [18,19].…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%